2021
DOI: 10.1108/ijchm-09-2020-1071
|View full text |Cite
|
Sign up to set email alerts
|

How do front-line employees make decisions on whether to hide their knowledge from co-workers in hospitality firms?

Abstract: Purpose This paper aims to explore the psychological process by which front-line employees (FLEs) in hospitality firms make decisions on hiding knowledge. Design/methodology/approach A qualitative methodology was used, with triangulated data collection from six different types of hospitality firms. By using the thematic analysis approach, a conceptual framework consisting of seven main themes was constructed to reflect the replicable logic of an individual’s knowledge exchange decision-making in various situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
(98 reference statements)
0
18
0
Order By: Relevance
“…However, there are limited studies about leaders who frequently hide knowledge in the workplace (Butt and Ahmad, 2019;Offergelt et al, 2019;Peng et al, 2019). This is also evident in less than a handful of empirical pieces on knowledge hiding behavior in the extant hospitality and tourism research (Lin et al, 2020;Rao et al, 2021;Zhao et al, 2016). Realizing such a potential area for inquiry, our paper tests the influence of LKH behavior on hotel employees' creativity and job performance.…”
Section: Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are limited studies about leaders who frequently hide knowledge in the workplace (Butt and Ahmad, 2019;Offergelt et al, 2019;Peng et al, 2019). This is also evident in less than a handful of empirical pieces on knowledge hiding behavior in the extant hospitality and tourism research (Lin et al, 2020;Rao et al, 2021;Zhao et al, 2016). Realizing such a potential area for inquiry, our paper tests the influence of LKH behavior on hotel employees' creativity and job performance.…”
Section: Contributionmentioning
confidence: 99%
“…Our paper investigating the aforesaid linkages is relevant and significant for at least three reasons. First, knowledge hiding is prevalent in many industries including the hospitality industry (Anser et al, 2021;Rao et al, 2021;Zhao et al, 2016). For example, a Chinese study reported that 46% of the individuals in the workplace engaged in different kinds of knowledge hiding behaviors (Peng, 2013).…”
Section: Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other authors disagree (Tedone and Bruk-Lee, 2021), arguing that conscientious individuals could avoid speaking out on work-related aspects, as they are likely to evaluate the risks involved. This could be related to knowledge hiding (Rao et al, 2021), caused by a lack of impulsiveness (Wang et al, 2020). In addition, conscientious employees have a certain orientation to be practical and proactive, so they may try to solve a given problem or situation themselves before sharing it with their supervisors, thus avoiding employee voice behaviour.…”
Section: Conscientiousnessmentioning
confidence: 99%
“…Thus, individuals who exhibit a low level of conscientiousness or a lack of direction could have more diverse thoughts and take risks, which would foster the contribution of original and valid suggestions for implementation. Highly conscientious employees' underlying lack of impulsiveness (Wang et al, 2020) could be also a reason for knowledge hiding (Rao et al, 2021) since they are in a position to have a longer period of time to analyse the potential rewards of knowledge disclosure.…”
Section: Analysis Of Receptionists' Personalitymentioning
confidence: 99%